Effect of topical heat therapy on clinical symptoms of peripheral neuropathy in patients with type II diabetes: A clinical trial - Ali Mohammadpour; Samane Najafi; Javad Bazeli; Mahnaz Parimoo (Tehran University of Medical Sciences, 2023)
Background & Aim: Diabetic neuropathy is found in 50% of people with diabetes and refers to a group of diseases that affect all nerves such as peripheral, autonomic and spinal nerves. This study aimed to investigate the effect of topical heat therapy on clinical symptoms of peripheral neuropathy in patients with type 2 diabetes. Methods & Materials: The present study was a randomized controlled clinical trial conducted on 52 patients with type 2 diabetes with peripheral neuropathy referred to the clinic of Allameh Behlool Gonabadi Hospital in 2018. The participants were randomly divided into two groups of intervention and placebo. The intervention group received heat therapy using a hot pack at 40 ° C twice a day for 20 minutes for a week. The control group received all routine care similar to the intervention group. A demographic information form and NSS questionnaire were used to collect the data through interview. Data were analyzed using the SPSS software version 23 at a significance level of less than 0.05. Results: The mean scores of neuropathy symptoms before and after the intervention were 5.46±1.90 and 4.12±1.55 respectively for the intervention group, and 4.88±1.53 and 5.08±1.52 for the control group that no significant difference was observed between the both groups before the intervention (P=0.23), but there was a statistically significant difference after the intervention (P=0.03). Also, the comparison of the mean scores of two groups after the intervention showed a significant difference (P<0.001). Conclusion: The findings showed that topical heat therapy can improve the clinical symptoms of peripheral neuropathy. Since this technique is easy to learn and inexpensive, it can be used to reduce treatment costs and drug side effects, as well as to improve patient self-care. Clinical trial registry: IRCT20181015041354N1